2022
DOI: 10.3390/microorganisms10102041
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillus paragasseri BBM171 Ameliorates Allergic Airway Inflammation Induced by Ovalbumin in Mice via Modulating the Th1/Th2 Balance

Abstract: Supplementation with specific probiotics has been shown to improve allergic airway symptoms. This study aimed to investigate immunomodulatory effects of a potential probiotic strain isolated from breast milk, Lactobacillus paragasseri BBM171 (BBM171), in an ovalbumin (OVA)-induced allergic mouse model. OVA-sensitized and OVA-challenged BALB/c mice were orally administered live or heat-inactivated BBM171 for 48 consecutive days. After the last allergen challenge, serum immunoglobulin (Ig) levels, inflammatory c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…GTB1 was administered to mice-induced airway inflammation. PBS was used as the control in this study to eliminate potential media-related effects ( Cheng et al, 2022 ; Bu et al, 2023 ; Duan et al, 2023 ). In our results, oral administration of the strain suppressed type 2 inflammation markers systemically (IgE in serum) and locally (type 2 cytokines and chemokines in BALF and lungs) proving that our target strain modulated the dysregulated immune system in an allergic airway inflammation model.…”
Section: Discussionmentioning
confidence: 99%
“…GTB1 was administered to mice-induced airway inflammation. PBS was used as the control in this study to eliminate potential media-related effects ( Cheng et al, 2022 ; Bu et al, 2023 ; Duan et al, 2023 ). In our results, oral administration of the strain suppressed type 2 inflammation markers systemically (IgE in serum) and locally (type 2 cytokines and chemokines in BALF and lungs) proving that our target strain modulated the dysregulated immune system in an allergic airway inflammation model.…”
Section: Discussionmentioning
confidence: 99%
“…The content of butyrate-producing bacteria Lactobacillus (from the Bacillota phylum) is reduced in patients with T2D. These bacteria have also been reported to have anti-allergic effects [34] and to modulate gene expression in a desirable direction tending toward the alleviation of diabetes [35].…”
Section: Relevance To Diabetesmentioning
confidence: 99%
“…Interestingly, the immunoregulatory function of inactivated probiotics has gradually attracted widespread attention. Cheng, et al [7] have demonstrated that HK-Lactobacillus paragasseri BBM171 can reduce airway inflammation in OVA-induced allergic mice by modulating serum immunoglobulin (Ig) levels, regulating the Th1/Th2 balance, decreasing levels of the pro-inflammatory cytokine interleukin (IL)-17, and increasing levels of the anti-inflammatory cytokine IL-10. And live L. paragasseri BBM171 and HK-L. paragasseri BBM171 had comparable alleviating effects.…”
Section: Introductionmentioning
confidence: 99%